(untitled) (IMC Journal of Medical Science, 2018)
Background and objectives: Ventilator-associated respiratory tract infection (VARTI) is a major cause of morbidity and mortality among the critically ill patients of intensive care units (ICU). Acinetobacter baumannii, an important offending pathogen in VARTI, has been found to be resistant to several antibiotics including carbapenems. The present study was conducted to determine the rate of New Delhi metallo-β-lactamase 1(NDM-1) producing A. baumannii causing VARTI among the patients admitted in an ICU of a large tertiary care hospital. Methods: The study was conducted from July 2013 to June 2014. Endotracheal aspirates (ETA) were collected from patients with clinically suspected VARTI. Samples were collected from patients who were on mechanical ventilation for more than 48 hours. ETA samples were cultured aerobically and isolated A. baumannii were tested for susceptibility to carbapenem. Presence of NDM-1 encoded by the blaNDM-1 gene was detected by polymerase chain reaction (PCR). Results: A total of 138 VARTI cases were included in the study. Total 107 (77.5%) bacteria were isolated from 138 ETA samples of which 38 were A. baumannii. Out of 38 isolated A. baumannii, 35 (92.1%) were resistant to imipenem/meropenem and 33 (86.8%) were positive for blaNDM-1 gene by PCR. Conclusion: The present study demonstrated that high proportion of A. baumannii isolated from VARTI cases in ICU were carbapenem resistant and blaNDM-1 positive. Careful infection control program should be considered to contain the spread of this multi-resistant organism to other hospital and community. IMC J Med Sci 2018; 12(1): 37-41